Characteristics of tropopause‐penetrating convection determined by TRMM and COSMIC GPS radio occultation measurements. Issue 14 (23rd July 2015) - Xian, Tao; Fu, Yunfei
Abstract Distribution and influence of convection in the upper troposphere and lower stratosphere have been investigated case by case or on regional to global scale. However, previous studies were limited by using proxies for convection or the bias of the tropopause data. Here the tropopause‐penetrating convection is investigated based on the sole use of observational products from Tropical Rainfall Measuring Mission (TRMM) precipitation radar data and Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC). The result shows that the frequency of precipitation‐top heights above the monthly mean tropopause in the tropics is reduced logarithmically if the cold‐point tropopause is adopted instead of the lapse‐rate tropopause. Using the collocated COSMIC and precipitation radar observations, the tropopause‐penetrating convection, i.e., the convection with the precipitation‐top height above the lapse‐rate tropopause, can be found over the summer monsoon regions and some continental regions. The averaged relative precipitation‐top heights of tropopause‐penetrating convective clusters are about 0.2–0.5 km without significant land‐ocean difference, while equivalent radii of clusters are 2.7–3.5 km over land and 0.2–0.5 km larger than those over ocean. These areal and vertical extents are smaller than those reported by previous studies. Furthermore, the collocated temperature profiles show that the tropopause‐penetrating convection generates warming in the upper troposphere and cooling near the lapse‐rate tropopause and in the lower stratosphere. Moreover, the tropopause‐penetrating convection leads to a rapid (within 20 min) lift of the lapse‐rate tropopause by the adiabatic lofting within the convection (within a 10 km radius).